2021
DOI: 10.3390/su13126583
|View full text |Cite
|
Sign up to set email alerts
|

Virtualization of Higher Education during COVID-19: A Successful Case Study in Palestine

Abstract: The purpose of the study is to explore students’ and faculty members’ responses to universities’ migration from face-to-face to online instruction as a result of the coronavirus (COVID-19) crisis. To this extent, a qualitative approach was used for data collection and involved a number of qualitative methods: an open-ended question survey, focus group discussion, social media data, and university reports. Additionally, a thematic analysis was used for data analysis. The findings of the study reveal that studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 34 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Suddenly, face-to-face universities around the world have been forced to progressively adapt new learning activities and different evaluation methodologies [ 5 , 6 ] derived from distance education [ 7 , 8 , 9 , 10 ] which, in principle, has meant the use of human resources. Furthermore, the impact of this precipitate transition to online education methods in engineering studies is still not fully known [ 11 ], and many challenges related to online education methods are still to be addressed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Suddenly, face-to-face universities around the world have been forced to progressively adapt new learning activities and different evaluation methodologies [ 5 , 6 ] derived from distance education [ 7 , 8 , 9 , 10 ] which, in principle, has meant the use of human resources. Furthermore, the impact of this precipitate transition to online education methods in engineering studies is still not fully known [ 11 ], and many challenges related to online education methods are still to be addressed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tosun et al [21] reported that in Turkey, the faculty and students did not have access to devices and the internet. Similar reports were shared for students from Palestine [35] where students reported non-availability of technological infrastructure. Sun et al [36] discussed that 90% of countries with high income delivered online education during Covid-19, while about 66% of countries with low income provided either online education and/or broadcast education.…”
Section: Disparity In Higher Education Caused By Technological Capabilitiesmentioning
confidence: 64%
“…This finding is in line with several previous studies conducted in a similar context. The use of social media was also happening some neighboring countries particularly during the COVID-19 pandemic, such as in Palestine (Affouneh et al, 2021;Marbán et al, 2021), Egypt (Al-Rahmi et al, 2021Al Mabruk et al, 2021), and Pakistan (Khan et al, 2021;T. M. Khan, 2021).…”
Section: Discussionmentioning
confidence: 99%